Targeting YAP1/TAZ in nonsmall‐cell lung carcinoma: From molecular mechanisms to precision medicine. Issue 4 (29th August 2022) - Mui, Chun Wai; Chan, Wai Nok; Chen, Bonan; Cheung, Alvin Ho‐Kwan; Yu, Jun; Lo, Kwok Wai; Ke, Huixing; Kang, Wei; To, Ka Fai
Abstract: Accumulating evidence has underscored the importance of the Hippo‐YAP1 signaling in lung tissue homeostasis, whereas its deregulation induces tumorigenesis. YAP1 and its paralog TAZ are the key downstream effectors tightly controlled by the Hippo pathway. YAP1/TAZ exerts oncogenic activities by transcriptional regulation via physical interaction with TEAD transcription factors. In solid tumors, Hippo‐YAP1 crosstalks with other signaling pathways such as Wnt/β‐catenin, receptor tyrosine kinase cascade, Notch and TGF‐β to synergistically drive tumorigenesis. As YAP1/TAZ expression is significantly correlated with unfavorable outcomes for the patients, small molecules have been developed for targeting YAP1/TAZ to get a therapeutic effect. In this review, we summarize the recent findings on the deregulation of Hippo‐YAP1 pathway in nonsmall cell lung carcinoma, discuss the molecular mechanisms of its dysregulation in leading to tumorigenesis, explore the therapeutic strategies for targeting YAP1/TAZ, and provide the research directions for deep investigation. We believe that detailed delineation of Hippo‐YAP1 regulation in tumorigenesis provides novel insight for accurate therapeutic intervention. Abstract :